2022
DOI: 10.1146/annurev-genom-111521-104455
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics and Typical Traits of Thoracic Aortic Aneurysm and Dissection

Abstract: Genetic predisposition and risk factors such as hypertension and smoking can instigate the development of thoracic aortic aneurysm (TAA), which can lead to highly lethal aortic wall dissection and/or rupture. Monogenic defects in multiple genes involved in the elastin-contractile unit and the TGFβ signaling pathway have been associated with TAA in recent years, along with several genetic modifiers and risk-conferring polymorphisms. Advances in omics technology have also provided significant insights into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 146 publications
0
33
0
Order By: Relevance
“…14 These genes encode regulatory molecules for the extracellular matrix (FBN1, FBN2, COL1A1, COL1A2, and COL3A1), the cytoskeleton in smooth muscle cells (ACTA2, MYH11, and MYLK), and the TGF-β signaling pathway (TGFβ2, TGFBR1, TGFBR2, SMAD3, and SLC2A10). 14 It is now well recognized that certain genes can alter the natural course of aortic disease by making patients more vulnerable to AAEs (such as rupture and dissection) at small aortic sizes, 15,16 well below the traditional intervention criteria, 17,18 and at a significantly younger age. This was first recognized for patients with mutations in the FBN1 gene (Marfan's syndrome), for whom the intervention criteria were lowered in the the American and European Aortic Disease guidelines.…”
Section: Genesmentioning
confidence: 99%
“…14 These genes encode regulatory molecules for the extracellular matrix (FBN1, FBN2, COL1A1, COL1A2, and COL3A1), the cytoskeleton in smooth muscle cells (ACTA2, MYH11, and MYLK), and the TGF-β signaling pathway (TGFβ2, TGFBR1, TGFBR2, SMAD3, and SLC2A10). 14 It is now well recognized that certain genes can alter the natural course of aortic disease by making patients more vulnerable to AAEs (such as rupture and dissection) at small aortic sizes, 15,16 well below the traditional intervention criteria, 17,18 and at a significantly younger age. This was first recognized for patients with mutations in the FBN1 gene (Marfan's syndrome), for whom the intervention criteria were lowered in the the American and European Aortic Disease guidelines.…”
Section: Genesmentioning
confidence: 99%
“…Prophylactic surgery of TAA patients reduces the mortality rate to approximately 5%, but comes along with a relatively high risk of complications [ 6 ]. To date, mutations in over 40 genes have been described to cause TAA [ 7 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these genes and others highlight the major molecular pathways involved in aortic biology: ECM adhesion and mechanosensing, vascular smooth muscle cell (VSMC) contractile function, and TGF-β (transforming growth factor beta) signaling, the latter of which regulates VSMC phenotype modulation from a contractile to a synthetic, proliferative state. 6,7 While family-based studies have provided a starting point for causal gene discovery, much remains unknown about the genetic basis of aortic traits, particularly in individuals with sporadic or late-onset forms of thoracic aortopathy. A small number of case-control exome sequencing studies in this population have identified rare variants in a small proportion of individuals, 6,9 but the lack of relative success with this approach suggests that low-frequency, high-impact mutations account for the minority of population-scale variation in aortic disease.…”
mentioning
confidence: 99%
“…Collectively, these genes and others highlight the major molecular pathways involved in aortic biology: ECM adhesion and mechanosensing, vascular smooth muscle cell (VSMC) contractile function, and TGF-β (transforming growth factor beta) signaling, the latter of which regulates VSMC phenotype modulation from a contractile to a synthetic, proliferative state. 6,7…”
mentioning
confidence: 99%